Creep behaviour of aluminium 7075 feedstock billet globular microstructure at high processing temperature - Megalingam, Arumugampillai; Asnul Hadi, Ahmad; Nasrul Azuan, Alang; Juliawati, Alias; Naher, Sumsun (Springer Nature, 2024)
This paper aims to present the determination of the creep behaviour of a globular microstructure aluminium 7075 alloy semi-solid metal feedstock billets under a constant temperature of 250 °C. Globular microstructures are often preferred in thixoforming processes due to their unique properties and favourable mechanical and high-temperature applications. Less attention has been given to globular microstructure even though the contribution of microstructure to creep behaviour is essential. Therefore, for this test, globular microstructure aluminium 7075 alloy feedstock billets were produced by the direct thermal method. The creep tests were conducted at different stress ranges from 30 to 70 MPa, and the effect of globular microstructure was examined. The results showed that the globular microstructure had the least deformation and the lowest creep rate at a longer deformation time. The fracture surface of the samples was then analysed with scanning electron microscopy (SEM). The microstructural changes that occurred during the test were investigated. SEM analysis revealed that the globular microstructure of the feedstock billet exhibits fewer voids and defects due to a uniform microstructure. The strain exponent value of globular microstructure billets was found to be at n = 4.6 in the stress range between 30 and 70 MPa at a constant temperature. This study is expected to provide an understanding of the creep behaviour of globular microstructures at high temperatures and high-stress conditions.